Show and Guide - Glória-Silva, Diogo (2024)
Funding Information: This work was supported by the FCT Ph.D. scholarship grant Ref. PRT/BD/152810/2021 awarded by CMU Portugal Affiliated Ph.D. program, and by the FCT project NOVA LINCS Ref. (UIDB/04516/2020). Data collection was possible under the Alexa Prize Taskbot Challenge organized by Amazon Science. Publisher Copyright: © 2024 Association for Computational Linguistics.